A Study on the Importance of Training and Development of Personnel of Jazan Port Authority, Saudi Arabia - Mohammed Saud Mira (MIRROR, 2018)
The maritime gateway to Saudi Arabia, Jazan is the fastest growing logistic centre emerging in to a major International transshipment terminal. An all-weather natural Port, and located strategically close to the busiest international sea routes Jazan is promoting a major liquid terminal, bulk terminal and maritime industries in its port based special economic zones. In this study, in the field of personnel management, training and development is the area concerned with managerial activities intended at enhancing the performance of individuals and groups in organizational surroundings. It has been branded by numerous names, including employee development, human resource development, and learning and development etc. Training, which comprises both on the job and off the job training methods and development certifies that uncertainty in organizational set-up, is reduced, and learning or behavioural alteration takes place in structured format. The clashes at workplace, with possibly the most disturbing and distressing career consequences, are those that take place between employees and their superiors. Training a staff to get along well with authority and with people who entertain diverse points of view is one of the best guarantees of long term accomplishment. For the study, 1% sample size (143) was considered out of the total population size of 14262 (Source: secondary data- Employee List as on 30.10.2017 from the Jazan port Authority website portal). The research design adopted in this study has been descriptive and analytical in nature. Both primary as well as secondary data has been used in this study along with proper sampling techniques.